Registro reciente de la martucha (Potos flavus) para la Reserva de la Biosfera Barranca de Metztitlán y el estado de Hidalgo, México - Hernández-Flores, Sergio Daniel; Vargas-Licona, Guadalupe; Aguilar-Miguel, Cristian; García-Becerra, Alejandro; García-Chávez, María del Carmen (Instituto de Ecología, A.C., 2018)
Based on the species survey conducted in the protected areas within Hidalgo state, we identified a hunted specimen of kinkajou in the southern portion of the municipality of Zacualtipan. The specimen was hunted during the first week of May 2016. We confirm the recent presence of the species in Hidalgo state and the Biosphere Reserve Barranca of Metztitlan. Hence, we expect to conduct more studies in this area that provide a better understanding of this taxon in Mexico and its association with vegetation loss.